Error on the Estimation of Sand Size Parameters When Using Small Diameter Sieves and a Solution - Lopez-Garcia, Patricia; Muñoz-Perez, Juan J.; Contreras, Antonio; Vidal, Juan; Jigena, Bismarck; Santos, Juan J.; Romero, Jeanette; Contreras, Francisco (Frontiers in Marine Science, 2021)
Analyses were carried out to determine the main sand size parameters (median grain size D50 and sorting σ) for beach nourishment purposes using the sieving method aboard a dredger. Due to a lack of space and the need to carry and use the material with ease, the sieves are commonly small (10 cm diameter), and the shaking procedure is usually performed by hand. However, the influence of shaking, either mechanically or manually, has not yet been studied with 10 cm diameter sieves. Therefore, 20 samples were taken from inside the hopper of a trailing suction dredger and sieved both manually and mechanically for 10 min. The results showed that manual sieving yielded higher D50 values than the mechanical procedure. The average error arising from using the manual method was 14%, but it can reach 36.5%. The granulometric analysis carried out for different shaking times has shown that this error is < 5% when at least 20 min of shaking is performed. The mechanical procedure gave always finer sand results. In addition, the overfill ratio calculated for both mechanical and manual results reached differences of up to 48%.